Recycling of Stoma Losses: A Good Practice for Neonates with High Output Stomas—Our Experience and Comparison with Literature. Issue 4 (December 2020) - Bindi, Edoardo; Molinaro, Francesco; Ferrara, Francesco; Fusi, Giulia; Taddei, Alessandra; Sica, Marina; Negro, Simona; Tomasini, Barbara; Detti, Rita; Ditta, Simona; Messina, Mario; Angotti, Rossella
Introduction: The recycling of proximal stoma losses is known as a good practice to manage patients with high output stoma. In our center, we introduced this practice about 10 years ago. We revised our series before and after recycling protocol and we reviewed the literature. Methods: This is a retrospective study. We included all neonates who underwent ileostomy between 2000 and 2019. They were divided into two groups, Group A and Group B, before and after the introduction of recycling of stoma losses. Demographic data were included. Outcomes evaluated to demonstrate the efficacy of stools recycling were: weight at the time of anastomosis and at discharge, length of total parenteral nutrition, and time (expressed in days) between anastomosis and passage of the stools. Data were analyzed using Student's t -test. P values <.05 were considered significant. Results: A total of 85 patients (29 females, 56 males) were included—Group A: 20 (24%) (13 males/7 females); Group B: 65 (76%) (43 males/22 females); Group A: 12/enterocolitis, 5/meconium-related ileum (MRI), 3/single intestinal perforation; Group B: 45 enterocolitis, 10/MRI, 8/single intestinal perforation, 1/an ileal atresia, 1/meconial peritonitis. Outcome about weight at anastomosis and discharge and about time of canalization were significant. Conclusion: We believe that the recycling of stoma losses is a safe and effective practice in neonates with ileostomy. Our technique of recycling is simple and practical. The benefit/risk rate is certain, in our opinion, in favor of the benefits as showed from our data.